The Role of School Autonomy in Promoting Collaboration and Competition Among Schools - Sulistianingsih, Sulistianingsih; Putra, Juniawan Mandala; Yusron, Ali; Saefudin, Arif; Harini, Hegar; Saddhono, Kundharu (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This article aims to determine the impact of education management reforms on school autonomy in encouraging collaboration and competition between schools conducted in Jakarta, Bogor, and Bekasi. This qualitative case study research was conducted over two months using data collection techniques through interviews, observation, and documentation. Semi-structured face-to-face interviews were conducted with 12 school principals in Jakarta, Bogor, and Bekasi, who were selected using purposeful sampling. Data analysis used triangulation techniques. The results showed that government decisions related to school autonomy and similar matters significantly influence relationships (collaboration and competition) between schools. The implications of these findings trigger a discussion on the impact of education management reforms aimed at increasing school autonomy in the context of school-to-school relationships. This study showed that educational management associated with school autonomy significantly influences relationships between schools. Decreasing the role of the state and increasing school autonomy exert different effects on school-to-school relationships depending on the governance model adopted. This study also shows that the experience of school collaboration and competition depends largely on the current policy of reorganizing school networks in cities and districts.